A Biblical Approach to Religious Life - Thomas Podimattam (Journal of Dharma, 1997)
In recent years several books dealing with various aspects of religious life have been published. But we have very few books which examine religious life entirely from a scriptural point of view. The book under review is a significant one in this direction. It examines almost every aspect of religious life in the light of the Bible. The Bible is the source of inspiration to religious life. Starting with vocation, the book disaiss practically every aspect of religious life. Vocation, a call from God or a choice by God, finds its explanation in God and in Him alone. The call of Abraham, and of the apostles, show how God out of his love chooses apparently unworthy individuals and makes them worthy instruments in His service. The same is true of the call of every religious person. The call to holiness is addressed to all, for there is only one holiness.